The Devil and Commodity Fetishism in South America - Taussig, Michael T. (Book collections on Project MUSE., 2010)
In this classic book, Taussig explores the social significance of the devil in the folklore of contemporary plantation workers and miners in South America. A new chapter for this anniversary edition features a discussion of Walter Benjamin and Georges Bataille that extends some of the ideas discussed in the original text.